Coronary artery aneurysms, insights from the international coronary artery aneurysm registry (CAAR). (15th January 2020) - Núñez-Gil, Iván J.; Cerrato, Enrico; Bollati, Mario; Nombela-Franco, Luis; Terol, Belén; Alfonso-Rodríguez, Emilio; Camacho Freire, Santiago J.; Villablanca, Pedro A.; Amat Santos, Ignacio J.; de la Torre Hernández, José M.; Pascual, Isaac; Liebetrau, Christoph; et al.
Abstract: Background: Coronary Aneurysms are a focal dilatation of an artery segment >1.5-fold the normal size of adjacent segments. Although some series have suggested a prevalence of 0.3–12%, data are lacking. In addition, they are not mentioned in practice guidelines. Our aim was investigate its prevalence, management and long-term outcomes. Methods and results: The coronary artery aneurysm registry (CAAR) involved 32 hospitals across 9 countries in America and Europe. We reviewed 436, 467 consecutive angiograms performed over the period 2004–2016. Finally, 1565 patients were recruited. Aneurysm global prevalence was 0.35%. Most patients were male (78.5%) with a mean age of 65 years and frequent cardiovascular risk factors. The main indication for angiogram was an acute coronary syndrome, 966 cases. The number of aneurisms was ≤2 per patient in 95.8% of the cases, mostly saccular, most frequently found in the left anterior descending and with numbers proportional with coronary stenosis. Aortopathies were related with more aneurysms too. Most patients received any revascularization procedure (69%), commonly percutaneous (53%). After a median follow-up of 37.2 months, 485 suffered a combined event (MACE) and 240 died. Without major differences comparing CABG vs PCI, MACE and death were more frequent in patients who received bare metal stents. Conclusions: Coronary artery aneurysms are not uncommon. Usually, they are associated with coronary stenosis and high cardiovascular risk. Antiplatelet therapy seems reasonable and a percutaneous approach is safe and effective. Highlights: The prevalence and long-term prognosis of coronary artery aneurysms is unclear. CAAR is a coronary artery aneurysm registry conducted in 32 hospitals in 9 countries. 436, 467 consecutive angiograms were reviewed, and 1565 patients included. Aneurysmal coronary artery disease is not uncommon in cath lab current practice. It is associated with high cardiovascular risk burden and high rate of events (>30%).